2016
DOI: 10.1289/ehp.1409277
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Health Impacts of Wildfire Smoke Exposure

Abstract: Background:Wildfire activity is predicted to increase in many parts of the world due to changes in temperature and precipitation patterns from global climate change. Wildfire smoke contains numerous hazardous air pollutants and many studies have documented population health effects from this exposure.Objectives:We aimed to assess the evidence of health effects from exposure to wildfire smoke and to identify susceptible populations.Methods:We reviewed the scientific literature for studies of wildfire smoke expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
772
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 880 publications
(861 citation statements)
references
References 87 publications
(198 reference statements)
20
772
0
16
Order By: Relevance
“…One recent review found that most studies with combined cardiovascular outcomes have found no significant associations, although some specific outcomes have been shown to be increased in the context of wildfire smoke, such as out‐of‐hospital cardiac arrest, heart failure, and ischemic heart disease 11. Another review found that 6 of 14 studies revealed statistically significant associations of wildfires and cardiovascular outcomes 12.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One recent review found that most studies with combined cardiovascular outcomes have found no significant associations, although some specific outcomes have been shown to be increased in the context of wildfire smoke, such as out‐of‐hospital cardiac arrest, heart failure, and ischemic heart disease 11. Another review found that 6 of 14 studies revealed statistically significant associations of wildfires and cardiovascular outcomes 12.…”
Section: Discussionmentioning
confidence: 99%
“…While the aim of this study was to explore cardiovascular and cerebrovascular health impacts attributable to wildfire smoke, respiratory outcomes were included for external validity, given the strong associations between wildfire‐PM 2.5 and respiratory disease that have been documented elsewhere, including asthma, COPD, and some respiratory infections such as pneumonia 11, 12. As with other studies, positive associations were found between wildfire smoke and asthma, COPD, pneumonia, and respiratory‐related chest pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations